¿Cuál es el bien jurídico protegido por el Art. 202.4 del Código Penal? Implicancias desde el D.Leg. 30076 y su práctica jurídico penal - Romero Romero, Jorge Luis (2024)
The legal asset protected in the 202.4 Article of the Penal Code has a particularity in its theoretical-practical application, and that is the wording of the criminal offense has led to the understanding that the criminal action must fall on real estate in possession; however, when the terminology refers: “those who have to oppose” is modified and included in the criminal offense, the hermeneutical and interpretative possibility arises that the passive subject is not only the immediate or mediate possessor of the property, but also the one who, in accordance with the legal framework, can support a right of a real estate or real nature; specifically, the owner. Along these lines, in this investigation the general theoretical foundations related to the legal good are presented, to extend the quality of passive subject of the usurpation crime to those subjects who, without having the status of possessor, have a right of a nature, real guarantee that they will resort to criminal proceedings to save their interests. Likewise, it should be noted that this research has a dogmatic nature, which aspires to contribute to the construction of a social rule of law state which constitutional rights are adequately recognized, leaving aside restrictive interpretations of the regulation that prevent effective prosecution of crime.